Modern paper crafts a 21st-century guide to folding, cutting, scoring, pleating, and recycling - Van Sicklen, Margaret; Gotch, Jen. (New York Stewart, Tabori & Chang, 2011)
More than 20 projects made using traditional paper craft techniques updated for the 21st century, from a leading author in the paper craft community.
"A Melanie Falick book."
Includes bibliographical references and index.
Keywords: Paper work; Handicaft